(untitled) (International Journal of Engineering and Computer Science, 2017)
In the era of globalization internet plays a vital role in all spheres of life and industries.Internet is very famous nowadays for satisfying people with various services related to various different fields. It is a very versatile facility which can help you in completing many tasks easily and conveniently with few clicks. It can be any work of daily usage or any specific service which needs a lot of research and formalities to be done beforehand, as well as this marketing is not an exception either. Online marketing, which is also called internet marketing, involves use of interactive,virtual spaces for the sake of promoting and selling goods and services. In fact, new synchronous, internet-based communication technologies had contributed to the restructuration of major economic sectors including marketing. Being cost-effective, flexible, and fast and enjoying an onunprecedented global reach, internet marketing has brought about different businesses incredible gainsrity, privacy, etc, emerged in the field of marketing from implementation of virtual space produce.